Investigations into the failure mechanisms of coal bursts based on a real burst event in the Tangshan coal mine - Jia, Dongxu; Zhi, Zengzhu; Cao, Chen; Zhang, Ming (Frontiers in Earth Science, 2023)
To investigate the failure mechanisms of coal bursts in the longwalls of underground coal mines, a case study based on the real coal burst in the Tangshan coal mine occurring on 2 August 2019 was carried out to analyze the cause and basic theories of the coal burst and, thus, propose approaches and methods to mitigate the damage. The coal burst occurred mainly due to the sliding of coal from the longwall ribs and the simultaneous uplifting of the floor. As a result of the longwall retraction, the roof above the coal seam was too stable to collapse, forming a long hanging roof behind the longwall. Because the longwall acted as a fulcrum, the hanging roof acted like a saw, exerting massive loads on the longwall. As a result, the roof in front of the longwall tended to slope upward, leaving the underlying coal seam unconfined. Due to the horizontal stresses, the longwall ribs collapsed into the longwall, causing the coal seam to break out. These findings could help improve the fundamental understanding of the failure mechanisms of coal breakouts and, thus, aid in the development of measures to prevent such occurrences.